Pengaruh Kualitas Website Dan Kualitas Service Terhadap Loyalitas Melalui Kepuasan Pengguna Shopee - Wahyu Widiya Ningsih; Ida Bagus Nyoman Udayana; Lusia Tria Hatmanti Hutami (JURNAL ILMIAH EDUNOMIKA, 2021)
This research was conducted with the aim of knowing and analyzing what could affect the loyalty of Shopee e-commerce users. With several variables contained in this study, namely, website quality, service quality, user satisfaction and loyalty. In this study, there is a population namely Shopee e-commerce users and customers. And sampled a number of 100 respondents who use and subscribe to Shopee e-commerce. In taking a sample in this study using a probability model sampling technique or random sampling. This technique is a sample return technique where each member of the population has an equal chance of being selected as a semple member. After processing the data with SPSS 20, this research shows that website quality and service quality have a positive effect on user satisfaction, and user satisfaction has a positive effect on loyalty. The results of these calculations show that the sig value is positive, therefore all variables are accepted because they have a positive influence. Keywords : website quality, service quality, user satisfaction, loyalty